Triple-negative and Her2-positive breast cancer in women aged 70 and over: prognostic impact of age according to treatment - Houvenaeghel, Gilles; Cohen, Monique; Gonçalves, Anthony; Berthelot, Axel; Chauvet, Marie Pierre; Faure, Christelle; Classe, Jean Marc; Jouve, Eva; Sabiani, Laura; Bannier, Marie; Tassy, Louis; Martino, Marc; et al. (Frontiers in Oncology, 2023)
Background: Elderly breast cancer (BC) patients have been underrepresented in clinical trials whereas ~60% of deaths from BC occur in women aged 70 years and older. Only limited data are available on the prognostic impact of age according to treatment, especially in the triple-negative (TN) and Her2-positive because of the lower frequency of these subtypes in elderly patients. We report herein the results of a multicenter retrospective study analyzing the prognostic impact of age according to treatment delivered in TN and Her2-positive BC patients of 70 years or older, including comparison by age groups. Methods: The medical records of 31,473 patients treated from January 1991 to December 2018 were retrieved from 13 French cancer centers for retrospective analysis. Our study population included all ≥70 patients with TN or Her2-positive BC treated by upfront surgery. Three age categories were determined: 70-74, 75-80, and > 80 years. Results: Of 528 patients included, 243 patients were 70-74 years old (46%), 172 were 75-80 years (32.6%) and 113 were >80 years (21.4%). Half the population (51.9%, 274 patients) were TN, 30.1% (159) Her2-positive/hormone receptors (HR)-positive, and, 18% (95) Her2-positive/endocrine receptors (ER)-negative BC. Advanced tumor stage was associated with older age but no other prognostic factors (tumor subtype, tumor grade, LVI). Adjuvant chemotherapy delivery was inversely proportional to age. With 49 months median follow-up, all patient outcomes (overall survival (OS), disease-free survival (DFS), breast cancer-specific survival (BCSS), and recurrence-free survival (RFS)) significantly decreased as age increased. In multivariate analysis, age >80, pT2-3 sizes, axillary macrometastases, lymphovascular involvement, and HR-negativity tumor negatively affected DFS and OS. Comparison between age >80 and <=80 years old showed worse RFS in patients aged > 80 (HR=1.771, p=0.031). Conclusions: TN and Her2-positive subtypes occur at similar frequency in elderly patients. Older age is associated with more advanced tumor stage presentation. Chemotherapy use decreases with older age without worse other pejorative prognostic factors. Age >80, but not ≤80, independently affected DFS and OS.